Pengaruh Kualitas Pelayanan, Price Discount, Store Atmosphere terhadap Pembelian Impulsif dengan Shopping Emotion Sebagai Variabel Intervening pada Konsumen Miniso Sunrise Mall Mojokerto - Sahri, Vania Berlinda Permata; Sari, Dewi Komala (Innovative Technologica: Methodical Research Journal, 2023)
This study aims to determine the effect of Service Quality, Price Discount, Store Atmosphere on Impulsive Purchases with Shopping Emotion as an Intervening Variable on Consumers of Miniso Sunrise Mall Mojokerto. This research uses quantitative research. The sample used includes 200 respondents. Samples were taken using total sampling technique. The data analysis technique used is PLS-SEM using the SmartPLS 3.2.9 program. The results of this study prove that service quality has a positive and significant effect on impulse buying, price discounts have a positive and significant effect on impulsive purchases, store atmosphere has a positive and significant effect on impulse purchases, service quality has a positive and significant effect on shopping emotion, price discounts have a positive and significant effect on shopping emotion. significant effect on shopping emotion, store atmosphere has a positive and significant effect on shopping emotion, shopping emotion has a positive and significant effect on impulse buying, service quality has a positive and significant effect on impulse buying through shopping emotion, price discount has a positive and significant effect on impulsive buying through shopping emotion, and store atmosphere has a positive and significant effect on impulse buying through shopping emotion.